Gender diversity in corporate boards: Evidence from quota-implied discontinuities - Olga Kuzmina; Valentina Melentyeva (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Using data across European corporate boards, we investigate the effects of quota-induced female representation on firm value and operations, under minimal identification assumptions. We consider sharp increases in the share of women on boards that arise due to rounding whenever percentage-based regulation applies to a small group of people. We find that having more women on corporate boards has large positive effects on Tobin's Q and buy-and-hold returns. This result is in stark contrast with previous empirical work that finds large negative effects. The reason for this discrepancy is that these papers considered firms with different pre-quota shares of women to be good counterfactuals to each other. In our data, we see that such firms had grown differently already before the regulation. Thus, assuming they are good comparables would result in a negatively biased estimate of the effect. Instead, we use quasi-random assignment induced by rounding and find that promoting gender equality is aligned with shareholder interests. This positive effect is not explained by increased risk-taking or changes in board composition, but rather by scaling down inefficient operations and empire-"demolishing".
Keywords: J16; G34; G38; D22; 330; Gender diversity; women on boards; gender quota; performance